Mirror‐Image Cofacial Coronene Dimers Characterized by CD and CPL Spectroscopy: A Twisted Bilayer Nanographene. Issue 11 (21st September 2021) - Uehara, Keiji; Kano, Haruka; Matsuo, Kyohei; Hayashi, Hironobu; Fujiki, Michiya; Yamada, Hiroko; Aratani, Naoki
Abstract: Bilayer graphene (BLG), which changes its electronic properties significantly depending on the interplanar distance and rotation angle, is a hot research topic. We successfully synthesized discrete BLG models by bridging two coronenes with a 1, 8‐naphthalene linkage (C2 ). Owing to the large rotational energy, the syn ‐ and anti ‐atropisomers of C2 could be isolated. X‐ray crystallographic analysis revealed that the syn ‐form (C2S ) is an AB stacking type and the anti ‐form (C2A ) is a chiral twisted bilayer graphene (TBG) type. Therefore, the anti ‐form of C2 was optically resolved and characterized by circular dichroism (CD) and circularly polarized luminescence (CPL) spectroscopy. The Cotton effect was observed in the CD spectra at the longest absorption wavelength, and the corresponding bisignate CPL spectra were observed. The dissymmetry factors | g lum | of C2A were found to be 2.0×10 −3 at 435 nm and 1.2×10 −3 at 450 nm. Abstract : A miniaturized version of bilayer graphene (BLG), which is currently being studied worldwide, was synthesized. Depending on the layering manner, two types of BLG model, AB stacking type and twist type, were formed. Since the latter has chirality, optical resolution was conducted to measure the chiroptical characteristics. Then, the clear Cotton effect was observed in both the CD and CPL spectra.